2020
DOI: 10.1007/s10620-020-06540-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Autoimmune Enteropathy and Its Associated Syndromes

Abstract: Autoimmune enteropathy is an extremely rare condition characterized by an abnormal intestinal immune response which typically manifests within the first 6 months of life as severe, intractable diarrhea that does not respond to dietary modification. Affected individuals frequently present with other signs of autoimmunity. The diagnosis is made based on a characteristic combination of clinical symptoms, laboratory studies, and histological features on small bowel biopsy. Autoimmune enteropathy is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Autoimmune enteropathy has been described as a component of inborn errors of immunity such as immunodysregulation polyendocrinopathy enteropathy X-linked (IPEX) and other disorders with loss of T-cell tolerance, as well as in association with other non-syndromic immune-mediated conditions and as an isolated disorder ( 10 ). Autoimmune enteropathy is a well-recognized complication of GVHD in patients following allogeneic HSCT; however, recipients of autologous transplants can also have auto-GVHD and autoimmune enteropathy ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune enteropathy has been described as a component of inborn errors of immunity such as immunodysregulation polyendocrinopathy enteropathy X-linked (IPEX) and other disorders with loss of T-cell tolerance, as well as in association with other non-syndromic immune-mediated conditions and as an isolated disorder ( 10 ). Autoimmune enteropathy is a well-recognized complication of GVHD in patients following allogeneic HSCT; however, recipients of autologous transplants can also have auto-GVHD and autoimmune enteropathy ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with STAT5b mutations present with growth failure and pulmonary disease while STAT1 mutations typically predispose to mucocutaneous candidiasis. Dysmorphic feature, developmental and growth delay and chronic lung disease are typical in ITCH mutation (23).…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Another study has shown that autoimmune enteropathies have also been previously discussed to cause carbohydrate malabsorption among pediatric patients and they are usually a group of disorders that affect the GIT in addition to the presence of other related organic comorbidities. 29,30 As previously mentioned that fat malabsorption and intestinal lymphangiectasia can lead to carbohydrate malabsorption and to develop a related manifestations. Inflammatory bowel diseases as Crohn's disease and ulcerative colitis have also been previously reported among studies in the literature review to cause carbohydrate metabolism in pediatric patients diagnosed with secondary.…”
Section: Carbohydrate Malabsorptionmentioning
confidence: 98%